Nanotechnology-based lipid systems applied to resistant bacterial control: A review of their use in the past two decades - dos Santos Ramos, Matheus Aparecido [UNESP] (2021)
The rate of infections caused by resistant bacteria to the antimicrobials available for human use grows exponentially every year, which generates major impacts on human health and the world economy. In the last two decades, human beings can witness the expressive increase in the Science and Technology worldwide, and areas such as Health Sciences have benefited from these advances in favor of human health, such as the advent of Pharmaceutical Nanotechnology as an important approach applied for bacterial infections treatment with resistance profile to available antibiotics. This review of the scientific literature brings the applicability of nanotechnology-based lipid systems as an innovative tool in the improvement of bacterial infections treatment. Important studies involving the use of liposomes, solid lipid nanoparticles, nanostructured lipid carriers, nanoemulsions, microemulsions and lipid nanocapsules were verified in the period from 2000 to 2020, where important scientific results were found and will serve as a basis for the use of these systems to remain in constant updating. This manuscript shows the use of these drug delivery systems as potential vehicles for antibacterial compounds, which opens a new hope in the complement of the antibacterial therapeutic arsenal. Important studies developed in the last 20 years are present in this review, and thus guarantees an update on the use of these drug delivery systems for researchers from different areas of Health Sciences.